INTERNATIONAL JURISDICTION RULES IN MATTERS OF PARENTAL RESPONSIBILITY IN THE EUROPEAN UNION AND BOSNIA AND HERZEGOVINA: THE CONCEPT OF HABITUAL RESIDENCE V. NATIONALITY - Jasmina Alihodžić (Human Research in Rehabilitation, 2012)
The rules of jurisdiction in matters of parental responsibility contained in the Brussels II bis Regulation are based on the concept of habitual residence, while the legislation in B&H in this area gave priority to the principle of nationality. Analyzing these concepts, the author of the paper points to the importance of interpreting the concept of habitual residence by the European Court of Justice, and gives possible directions for reform of the relevant provisions of the PIL Act in terms of their compliance with EU law.